2018
DOI: 10.1007/s00244-018-0512-3
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutants Residues in Human Breast Milk from Bathinda and Ludhiana Districts of Punjab, India

Abstract: In the present study, persistent organic pollutants (POPs), including six congeners of polychlorinated biphenyls (PCBs) and organochlorine pesticides, were estimated in human breast milk samples collected from two districts of Punjab (India). The mean concentrations of POP residues were recorded higher in Bathinda district (PCBs: 33.7; DDTs: 519.2; HCHs: 46.6 ng g lipid wt.) than Ludhiana (PCBs: 24.2; DDTs; 415.3; HCHs; 35.5 ng g lipid wt.). Levels of PCBs and DDTs were observed higher in primiparas, whereas H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 45 publications
1
8
1
Order By: Relevance
“…The limit of detection (LOD) in our screening study is also higher (10 μg/L; LOQ of 25 μg/L for OCs) than those in the published literature from India, which range between 0.008-0.02 μg/L [31]; 0.001 μg/L (OCPs) and 0.002 μg/L (OPs and SPs) [30]. It is important to note that our LODs (10 μg/L) were below maximum residue levels of 0.05 mg/kg (50 μg/L) set by the FAO/ WHO for DDTs in milk, thus allowing us to detect trace concentrations and values of public health significance [43].…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…The limit of detection (LOD) in our screening study is also higher (10 μg/L; LOQ of 25 μg/L for OCs) than those in the published literature from India, which range between 0.008-0.02 μg/L [31]; 0.001 μg/L (OCPs) and 0.002 μg/L (OPs and SPs) [30]. It is important to note that our LODs (10 μg/L) were below maximum residue levels of 0.05 mg/kg (50 μg/L) set by the FAO/ WHO for DDTs in milk, thus allowing us to detect trace concentrations and values of public health significance [43].…”
Section: Discussioncontrasting
confidence: 56%
“…Another study conducted in the north Indian state of Punjab found mean breastmilk concentrations of p,p'-DDE at 0.00056 ± 0.0042 μg/L [30]. More recently, Bawa et al, [31] found p,p'-DDE at 0.407 ± 0.885 and 0.345 ± 0.815 μg/L lipid weight from the north Indian cities of Bathinda and Ludhiana. They also detected DDT at 0.519 ± 1.017 and 0.415 ± 0.846 μg/L lipid weight in both cities respectively [31].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Pesticides are highly toxic, persistent and bio-accumulative in nature [ 4 , 5 ]. Due to their lipophilic characteristics, they get biomagnified in the food chain and may cause serious health consequences [ 6 , 7 ].…”
Section: Additional Informationmentioning
confidence: 99%